1988
DOI: 10.1002/jrs.1250190108
|View full text |Cite
|
Sign up to set email alerts
|

Laser Raman and infrared spectra of Rochelle salt crystals

Abstract: A systematic analysis of the IR and Raman spectra of Rochelle salt (NaKC,H,O, * 4H,O) in terms of the standard frequency correlations, deuteration shift and typical nature (with respect to intensity and width) of bands due to different modes is reported. The bands due to the internal modes (excluding some skeletal modes) of the C,H,O:-ion appear as doublets. For certain modes 1e.g. PCH, vC(OH) and &oo)] doublets arise owing to interactions between two identical oscillations of two identical groups in COO(HO)HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
(10 reference statements)
3
9
0
Order By: Relevance
“…The Raman vibrational bands observed at 1546, 1447, 1396 and 1374 cm -1 in RbHT and 1467, 1444 and 1417 cm -1 in SrTT are assigned to the ν a CO and ν s CO modes. These assignments agree with the assignments for K 2 C 4 H 4 O 6 .1/2H 2 O crystals (BHATTACHARJEE et al,1988). A broad and doublet nature of ν a CO and ν s CO bands have been observed for RbHT crystals.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The Raman vibrational bands observed at 1546, 1447, 1396 and 1374 cm -1 in RbHT and 1467, 1444 and 1417 cm -1 in SrTT are assigned to the ν a CO and ν s CO modes. These assignments agree with the assignments for K 2 C 4 H 4 O 6 .1/2H 2 O crystals (BHATTACHARJEE et al,1988). A broad and doublet nature of ν a CO and ν s CO bands have been observed for RbHT crystals.…”
Section: Resultssupporting
confidence: 87%
“…In SrTT crystals, βCH vibrational mode are observed as strong at 1296 and 1287 cm -1 (IR) and 1289 cm -1 (Raman). In Raman spectra of K 2 C 4 H 4 O 6 .1/2H 2 O (BHATTACHARJEE et al,1988) and NaKC 4 H 4 O 6 .4H 2 O (BHATTACHARJEE et al, 1989) the band in this region is also reported to be due to the βCH mode of C 4 H 4 O 6 2ion. In secondary alcohol's, the CHOH group and νC(OH) vibrational bands generally appear in the region 1050 -1150cm -1 (COLTHUP et al).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] An analysis of Eqns (2j(4) leads to the following inferences :…”
Section: Salient Features Of the Theoriesmentioning
confidence: 99%